DEVELOPING QUARTET CARD GAMES FOR TEACHING VOCABULARY (A Case of the Eighth Grade Students of SMP Islam Al Madina Semarang in the Academic Year of 2014/2015) (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2015)
Vocabulary is an important aspect of language development. Teaching vocabulary is getting crucial nowadays especially in junior high school. However, some English teachers cannot provide appropriate English teaching media. Commonly some English teachers taught vocabulary in random topics. The vocabulary teaching media was less interesting. This study has three aims. First, to explain the problems of the English teacher and the eighth grade students of SMP Islam Al Madina Semarang. Second, to explain the needs vocabulary of the English teacher and the eighth grade students of SMP Islam Al Madina Semarang. Third, to show how to develop effective Quartet Card Games to enrich vocabulary. There are two subjects of the research. First, the eighth grade students of SMP Islam Al Madina Semarang in the academic year of 2014/2015. Second, the English teacher of SMP Islam Al Madina Semarang. R&D (Research and Development) approach was adopted in this study. The study revealed that the problem faced by the English teacher was lack of media for teaching vocabulary. The students were bored of vocabulary learning. The need analysis showed that the students needed various vocabulary items. The English teacher believed that the vocabulary teaching media should be interesting and colorful. Through the process of drafting, trying out, and refining the Quartet Card Games it was found that some cards contained ambiguities. To avoid any ambiguity check (âˆš) and cross (x) signs were added to some cards. It is suggested that the teacher choose appropriate vocabulary teaching media. It is also suggested that further research is conducted to gain better understanding of the vocabulary teaching media.